2020
DOI: 10.1177/0037549720914749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating intensive care unit admission and discharge policies using a discrete event simulation model

Abstract: The efficient utilization and management of a scarce resource such as the intensive care unit (ICU) is critical to the smooth functioning of a hospital. This study investigates the impact of a set of operational policies on ICU behavior and performance. Specifically, the implemented policies are (a) wait time thresholds on how long patients can wait for an ICU bed, (b) the time windows during which patient discharges and transfers take place, and (c) different patient mix combinations. The average waiting time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Similarly, Grida and Zeid 44 developed a systems dynamics simulation model of a medium-sized hospital with the focus of their analysis being identification of throughput improvement policies for the surgical department via a theory of constraints approach. Of the third type, Hasan et al 45 developed a DES of an ICU in a hospital catering to patients of multiple types from upstream hospital units, such as the ED, elective surgery, and emergency surgery. The objective of the study was to find suitable admissions and discharge policies to improve both patient and provider outcomes.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Similarly, Grida and Zeid 44 developed a systems dynamics simulation model of a medium-sized hospital with the focus of their analysis being identification of throughput improvement policies for the surgical department via a theory of constraints approach. Of the third type, Hasan et al 45 developed a DES of an ICU in a hospital catering to patients of multiple types from upstream hospital units, such as the ED, elective surgery, and emergency surgery. The objective of the study was to find suitable admissions and discharge policies to improve both patient and provider outcomes.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…operations 24 ) or a single hospital unit (e.g. laboratory 25 ; ED 26,27,28 ; radiology 29 ; OR 30 ; ICU 31 ). The authors are not aware of any works in the literature that take a similar whole-hospital approach.…”
Section: Discussionmentioning
confidence: 99%
“… 20 The participants in this study also reported changes to ICU triage criteria through triaging patients out of the ICU based on acuity if a surge occurred, caring for patients in the progressive care unit instead of the ICU, and disallowing COVID-19 trauma patients in the ICU. Hasan et al 2 22 evaluated ICU admission and discharge policies and reported that increasing discharge windows, the times of the day when patients are considered for discharge, significantly lowered the average wait times for ICU admission, and increased the amount of patients able to be admitted to the ICU. Revising ICU discharge criteria during COVID-19 could allow for more patients in need of an ICU bed to be admitted.…”
Section: Discussionmentioning
confidence: 99%